RESEARCH FOR Mycoplasma spp IN MILK SAMPLES FROM MASTITIC COWS. - FRANCHESCHINI, V. M.; NOGUEIRA, M. F.; VICTORIA, C.; SILVA, R. C.; LANGONI, H. (Ars Veterinaria, 2008)
Many species of mycoplasmas account for cases and outbreaks of mastitis in dairy herds worldwide. Mastitis due to mycoplasma in Brazil was first reported only in 1996, and its real importance in the national cases of the disease is unknown. Mycoplasmas are highly contagious agents and its control depends on sick cow detection and slaughtering. In this study, which was carried out in mid-western region of São Paulo State, Brazil, 101 and 121 samples of lacteal secretion derived from acute clinical mastitic cows and subclinical cases, respectively, were inoculated in modified Hayflick mediums. Also, all the samples underwent a molecular analysis by PCR technique with Mycoplasma genus specific primers. All samples were negative for Mycoplasma in the Hayflick modified medium, as well as in the PCR. KEY-WORDS: Mastitis. Mycoplasma. PCR.